CUSTOMER AND CONSUMER RELATIONSHIP MANAGEMENT TOWARDS E-BUSINESS STRATEGIES - Kala, K. (International Journal of Research -GRANTHAALAYAH, 2017)
E-Commerce is an emerging technology for purchasing and selling of products through electronically. It is the commercial transaction which involves transfer of information over the internet. It changes the way to do business. With advancements in technology, there may be a chance to change. Customer Relationship Management and Consumer Relationship management play an essential role with E-Business. The focusing scenarios are facing many pros and cons by E-Business. This Paper makes an attempt to highlight the benefits and drawbacks in these scenarios.